2018
DOI: 10.3390/ijms19020386
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Predicted Ligand Binding Sites and Molecular Docking Analysis of Slc2a4 as a Therapeutic Target for the Treatment of Cancer

Abstract: Presently, many studies have focused on exploring in silico approaches in the identification and development of alternative therapy for the treatment and management of cancer. Solute carrier family-2-member-4-gene (Slc2a4) which encodes glucose transporter 4 protein (GLUT4), has been identified as a promising therapeutic target for cancer. Though Slc2a4 is known to play a major regulatory role in the pathophysiology of type 2 diabetes, emerging evidence suggests that successful pharmacological inhibition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 46 publications
2
30
0
5
Order By: Relevance
“…Both processes converged in two models that were later analyzed by PROCHECK software, in order to check the stereochemical quality of the protein structure and analyze its overall and residue-by-residue geometry. The obtained results indicated that homology modeling presented appropriate quality parameters ( Figure 5 ) [ 12 ], with values similar to the ones reported in other very interesting works [ 29 , 30 ]. Given this, studies were continued with the homology model of hDKC1.…”
Section: Discussionsupporting
confidence: 85%
“…Both processes converged in two models that were later analyzed by PROCHECK software, in order to check the stereochemical quality of the protein structure and analyze its overall and residue-by-residue geometry. The obtained results indicated that homology modeling presented appropriate quality parameters ( Figure 5 ) [ 12 ], with values similar to the ones reported in other very interesting works [ 29 , 30 ]. Given this, studies were continued with the homology model of hDKC1.…”
Section: Discussionsupporting
confidence: 85%
“…The predicted hydrophobic value of the AMPs was greater than 30% as anticipated for an ideal AMP and these values contributed significantly to their high binding potential to receptors and cells. 29 This work is in accordance with the work of Aruleba et al, 30 where AMPs were used to investigate the structural and predicted binding sites of Slc2a4 as a therapeutic target in the treatment of cancer.…”
Section: Putative Amps Discovery and Their Physicochemical Characterisupporting
confidence: 55%
“…Jarak antara bagian permukaan makromolekul enzim dan molekul peptida bioaktif dibatasi dengan batas radius maksimum 4.0 Å. Studi penambatan molekuler ini menggunakan parameter dengan berdasar pada representasi bentuk molekul, bagian sisi aktif pengikatan makromolekul target, serta pemilihan dan penilaian. Studi penambatan molekuler ini juga dilakukan secara efisien tanpa adanya ikatan antar molekul yang bersifat rigid (Aruleba et al, 2018).…”
Section: Studi Penambatan Molekuler Berbasis Protein-peptidaunclassified